Stage dependent toxicity of Bisphenol A on Rhinella arenarum (Anura, Bufonidae) embryos and larvae - Hutler Wolkowicz, Ianina Ruth (2011)
The acute and chronic toxicity of bisphenol A (BPA) was evaluated on the common South American toad Rhinella arenarum embryos and larvae by means of continuous and pulse exposure treatments. Embryos were treated continuously from early blastula (S.4) up to complete operculum (S.25), during early larval stages and by means of 24 h pulse exposures of BPA in concentrations ranging between 1.25 and 40 mg L−1, in order to evaluate the susceptibility to this compound in different developmental stages. For lethal effects, S.25 was the most sensitive and gastrula was the most resistant to BPA. The Teratogenic Index for neurula, the most sensitive embryonic stage for sublethal effects was 4.7. The main morphological alterations during early stages were: delayed or arrested development, reduced body size, persistent yolk plug, microcephaly, axial/tail flexures, edemas, blisters, waving fin, underdeveloped gills, mouth malformations, and cellular dissociation. BPA caused a remarkable narcotic effect from gill circulation stage (S.20) onwards in all the organisms exposed after 3 h of treatment with 10 mg L−1 BPA. After recovering, the embryos exhibited scarce response to stimuli, erratic or circular swimming, and spasmodic contractions from 5 mg L−1 onwards. Our results highlight the lethal and sublethal effectsof BPA on R. arenarum embryos and larvae, in the last case both at structural and functional levels.